WESTERN BALKANS IN THE RUSSIAN-UKRAINIAN WAR: THE INSTRUMENTALIZATION OF THE PAST THROUGH DOMINANT POLITICAL DISCOURSES IN THE MEDIA - Surlic, Stefan; Milić, Kristina (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The beginning of the Russian invasion of Ukraine has led to global tectonic changes that have also affected the countries of the Western Balkans. Due to the absence of confrontation with the past and unresolved status issues, the interpretations of the war in Ukraine received the expected self-projection.discourses, the narrative revival of old conflicts, and the strengthening of antagonisms on a national basis. In the political sphere, a self-victimizing discourse was created as another means ofinstrumentalizing the past conflict. The author’s intention is to answer the question of how the war in Ukraine, through the dominating discourses of the political elites in Serbia, Croatia, Bosnia, and Herzegovina and Kosovo, confirm the already existing ethnicized and one-sided views of the past. The authors used critical discourse analysis with a methodological approach based on the discourse historical method (Wodak, 2001), which, by placing the topic in a specific socio-political context, willshow how the instrumentalization of the Russian-Ukrainian conflict by leaders becomes very useful for strengthening internal political support regarding sensitive national and status issues.